Imagined liberation : xenophobia, citizenship, and identity in South Africa, Germany, and Canada - Adam, Heribert; Moodley, Kogila (Politics, history, and social change., 2015)
On a spectrum of hostility towards migrants, South Africa ranks at the top, Germany in the middle and Canada at the bottom. South African xenophobic violence by impoverished slum dwellers is directed against fellow Africans. "Foreign" Africans are blamed for a high crime rate and most other maladies of an imagined liberation. Why would a society that liberated itself in the name of human rights turn against people who escaped human rights violations or unlivable conditions at home? What happened to the expected African solidarity? Why do former victims become victimizers?With porous borders, So.